Inflammatory Drug-Resistant Epilepsy Index (IDREI) as a Molecular Compound Biomarker in Focal Epilepsies - Maria José Aguilar-Castillo; Guillermo Estivill-Torrús; Guillermina García-Martín; Pablo Cabezudo-García; Yolanda López-Moreno; Jesús Ortega-Pinazo; Teresa Ramírez-García; Nicolas Lundahl Ciano-Petersen; Pedro Jesus Serrano-Castro (Biomolecules)
Background: There is growing evidence that neuroinflammation is involved in epileptogenesis. Identifying its biomarkers can be important for distinguishing epilepsy patients from healthy individuals and differentiating well-controlled epilepsy from drug-resistant epilepsy (DRE). Methods: An observational case-control study at Malaga’s Regional University Hospital involved epilepsy patients divided into three groups: healthy controls (HC), seizure-free epilepsy (SFE), and DRE. Demographic and clinical data and plasmatic and/or CSF levels of 24 different inflammation-related molecules were collected for each patient and were analyzed through univariate and multivariate analysis. Results: The study included 68 patients: 38 in the DRE group, 14 in the SFE group, and 16 in the HC group. A new Inflammatory Drug-Resistant Epilepsy Index (IDREI) was created using key variables with significant or trending significance. This index combined pro-inflammatory mediators (ICAM-1 and NfL) and anti-inflammatory factors (IL-10 and IL-4), showing statistical significance (p = 0.002). ROC curve analysis for the IDREI gave an AUC of 0.731 (95% CI: 0.608–0.854). A multivariate logistic regression model’s ROC analysis resulted in a higher AUC of 0.891 (95% CI: 0.791–0.991). Conclusions: The IDREI molecular index shows promise in predicting epilepsy and drug-resistant epilepsy (DRE). Additional prospective studies are required to assess its clinical utility.